Robust Multivariable controller Design with the simultaneous H2 /H∞/µ for Single Person Aircraft - Javad Mashayekhi Fard; Mohammad Ali Nekoui; Ali Khaki Sedigh; Roya Amjadifard (International Journal of Electrical and Computer Engineering (IJECE), 2013)
In a physical system several targets are normally being considered in which each of nominal and robust performance has their own strengths and weaknesses. In nominal performance case, system operation without uncertainty has decisive effect on the operation of system, whereas in robust performance one, operation with uncertainty will be considered. The target of present paper is a balance between nominal and robust performance of state feedback A new approach of present paper is the combination of two controllers of μ and H2/H∞.  The controller for robust stability status, nominal performance, robust performance and noise rejection are designed simultaneous. Controller will be achieved from solving constraint optimization problem. Where a simultaneous H2 /H∞/µ robust multivariable controller has been designed over an X-29 Single Person.  This model has three inputs and three outputs, where the state space equations of the system response to an unstable one. Simulation results show the effectiveness and benefits of the method.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2352